In the womb : animals - Sims, Michael, 1958-; National Geographic Society (U.S.) (Washington, D.C. : National Geographic, 2009)
Shows and explains the prenatal development of dogs, dolphins, kanagroos, and elephants.
Familiar -- Extraordinary -- Extreme.
Based on two television documentaries about animals in the womb.
Includes bibliographical references (p. 156-157).
Keywords: Embryology -- Pictorial works; Fetus -- Development -- Pictorial works; Embryologie -- Ouvrages illustr; F{u4D73} -- Deloppement -- Ouvrages illustr